Neglecting the neglected: Tobacco cessation support is 'essential' for the management of asthma and COPD - Dilek Karadogan; İlknur Kaya; Merve Yumrukuz Şenel; Esin Bilgin Konyalıhatipoğlu; Tahsin Gökhan Telatar; Metin Akgün (Tobacco Induced Diseases)
Introduction Asthma and COPD management have a broad framework, and smoking cessation plays an essential role. We examine the management of asthma and COPD patients not only for inhaler treatment options but also for essential interventions, such as smoking cessation support.